2019
DOI: 10.1080/13691058.2019.1614671
|View full text |Cite
|
Sign up to set email alerts
|

Constructing, reproducing and challenging masculinities in a participatory intervention in urban informal settlements in South Africa

Abstract: Participatory interventions with men and boys to transform masculinities are increasingly common to improve health and reduce intimate partner violence and HIV-related risk. Yet, despite this, there has been little consideration of how facilitators' own masculinities shape interventions. In this analysis of Stepping Stones and Creating Futures, a gender-transformative programme delivered to young men (aged 18-30 years) in urban informal settlements in Durban, South Africa we explore how facilitators' masculini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Traditionally, IPV inter ventions have pri mar ily focused on empowering women and expos ing them to mes sages about gen der equal ity (Alexander and Welzel 2015;Pierotti et al 2018;Wyrod 2008). Recently, pro grams have begun to focus more atten tion on chal leng ing the gen dered cul tural under stand ings of men and prompting behav ior change to reduce the prev alence of IPV (Barker et al 2010;Casey et al 2018;Gibbs et al 2019;Pierotti et al 2018). Despite some suc cess, these male-cen tered ini tia tives have been met with resis tance, par tic u larly when they threaten to under mine the fun da men tal expec tation that women be sub or di nate to their hus bands (Pierotti et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, IPV inter ventions have pri mar ily focused on empowering women and expos ing them to mes sages about gen der equal ity (Alexander and Welzel 2015;Pierotti et al 2018;Wyrod 2008). Recently, pro grams have begun to focus more atten tion on chal leng ing the gen dered cul tural under stand ings of men and prompting behav ior change to reduce the prev alence of IPV (Barker et al 2010;Casey et al 2018;Gibbs et al 2019;Pierotti et al 2018). Despite some suc cess, these male-cen tered ini tia tives have been met with resis tance, par tic u larly when they threaten to under mine the fun da men tal expec tation that women be sub or di nate to their hus bands (Pierotti et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other IPV prevention programmes have similarly found that male participants sometimes rebelled against or resisted intervention messages ( McGeeney, 2015 ; Pierotti et al , 2018 ). A study in South Africa described ways in which male facilitators of an IPV prevention intervention negotiated and engaged their own masculinities—sometimes limiting the potential of the programme to contribute to transformational change ( Gibbs et al , 2019 ). These examples are in line with the finding from a recent systematic review that gender-based violence interventions appear more effective at reducing exposure to IPV among young women than at reducing exposure or perpetration among young men ( Meinck et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other papers from these data sets have discussed the difficulty of shifting men's headship roles and patriarchal power in Rwanda (Stern, Heise and McLean 2018) and South Africa (Gibbs et al 2020). An earlier evaluation of Stepping Stones with adolescents in South Africa found that women showed greater assertiveness and some agency in HIV risk reduction, yet the majority did not challenge their male partners or the cultural norms of conservative femininities (Jewkes, Wood and Duvvury 2010).…”
Section: Discussionmentioning
confidence: 99%